(untitled) (Colloquia Comparativa Litterarum, 2025)
Angel V. Angelov. Philology, Literature and Symbolic Geography of Europe: Erich Auerbach, Leo Spitzer, Edward Said, Stefan Zweig, Hugo von Hofmannsthal. Sofia, Bulged, 2022. https://litclub.bg/library/fil/angelvangelov/kniga2022.pdf